Toward Patient-Centered Stewardship of Research Data and Research Participant Recruitment With Blockchain Technology - Zhang, Peng; Downs, Chris; Le, Nguyen Thanh Uyen; Martin, Cory; Shoemaker, Paul; Wittwer, Clay; Mills, Luke; Kelly, Liam; Lackey, Stuart; Schmidt, Douglas C.; White, Jules (Frontiers in Blockchain, 2020)
Significant effort is required to recruit and validate patients for research studies. Researchers are typically limited to patients that they have a physical touchpoint with (e.g., patients at VUMC). This physical access limitation reduces the research attention that patients with rare diseases with little geographic concentration and poorer patients in rural areas receive. This paper explores the use of mobile computing and blockchain technology to provide validation of research studies and their data usage, advertisement of research studies, collection of research data, and sharing of data across studies. The paper presents key challenges of using blockchains and mobile computing to solve these issues, competing architectural approaches, and the benefits/trade-offs of each approach.